Implications of positive psychology in community service guidance practice: A group intervention for community children - Qin, Yusu; Gao, Shujuan; Zhang, Yu; Shi, Linsong; Huang, Chen; Bao, Wanling; Peng, Chongchuan; Zhang, Xue (International Journal of Educational Studies, 2023)
Positive Psychology Interventions (PPIs) has been widely used in the world with children and has achieved good results. In recent years, PPIs has been carried out among college students in China and has achieved certain results. In contrast, there is little use in Chinese children. In order to verify the effect of PPIs on children in Chinese communities, so that we can provide an effective way to serve children in the community. This study adopted the method of experimental research, and compared the effect of PPIs on the improvement of positive psychological quality of children in communities by pre - and post-test. The results showed that through PPIs, the positive psychological quality of children in the community was significantly improved, and it was not affected by gender, grade and whether they came from a single parent family. But this improvement is only an overall improvement, not an improvement in every quality. Which quality can be improved depends on which PPIs program is used. Therefore, this study suggests that PPIs can be widely used in children in the community, but it needs to be measured before intervention, and the appropriate PPIs program should be accurately selected according to the measured results.